Isolation, tradition, or tourism? The preservation of traditions in the art of Taquile Island - Lake Titicaca in the context of neoliberalism - Ordoñez Hidalgo, Bruno (2025)
The art of Taquile Island is known for its unique characteristics that distinguish it from other locations in the Lake Titicaca region, including its musical style, textile iconography, spinning and weaving techniques, instrumental cycle, etc. The discourse disseminated by academic and non-academic sources about the isolation of Taquile society is often used to explain the greater preservation and “purity” of its culture in aspects such as political organization, religion, language, etc. This discourse is also reproduced with regard to its art, without taking into account the role played by other aspects such as the consolidation of tourism as its main economic activity or the ongoing construction of its local identity. In this context, this research aims to explain the preservation of Taquile’s cultural identity through its artistic expressions, analyzing the social and economic factors involved, such as the discourse reproduced by the Taquileños regarding the preservation of their artistic tradition, the meaning given to variations in local artistic characteristics, and the role played by the discourse of isolation, respect for tradition, and the phenomenon of the commercialization of ethnicity in the construction of their artistic identity.Findings included the exoticization of the island’s relative isolation, the importance of maintaining traditions for the people of Taquile, and the important role of tourism in the continued reproduction of traditions.